Encyclopedia of law and higher education - Jusso, Charles J. (SAGE Publications, 2010)
The Encyclopedia of Law and Higher Education is a compendium of information that tells the story of law and higher education from a variety of perspectives. As many of the entries in this encyclopedia reflect, the editor and contributors have sought to place legal issues in perspective so that students of higher education and the law can inform policy makers and practitioners about the meaning and status of the law and also raise questions for future research as they seek to improve the quality of learning for all